Interaction between the Oral Microbiome and Dental Composite Biomaterials: Where We Are and Where We Should Go. (September 2020) - Kreth, J.; Merritt, J.; Pfeifer, C.S.; Khajotia, S.; Ferracane, J.L.
Dental composites are routinely placed as part of tooth restoration procedures. The integrity of the restoration is constantly challenged by the metabolic activities of the oral microbiome. This activity directly contributes to a less-than-desirable half-life for the dental composite formulations currently in use. Therefore, many new antimicrobial dental composites are being developed to counteract the microbial challenge. To ensure that these materials will resist microbiome-derived degradation, the model systems used for testing antimicrobial activities should be relevant to the in vivo environment. Here, we summarize the key steps in oral microbial colonization that should be considered in clinically relevant model systems. Oral microbial colonization is a clearly defined developmental process that starts with the formation of the acquired salivary pellicle on the tooth surface, a conditioned film that provides the critical attachment sites for the initial colonizers. Further development includes the integration of additional species and the formation of a diverse, polymicrobial mature biofilm. Biofilm development is discussed in the context of dental composites, and recent research is highlighted regarding the effect of antimicrobial composites on the composition of the oral microbiome. Future challenges are addressed, including the potential of antimicrobial resistance development and how this could be counteracted by detailed studies of microbiome composition and gene expression on dental composites. Ultimately, progress in this area will require interdisciplinary approaches to effectively mitigate the inevitable challenges that arise as new experimental bioactive composites are evaluated for potential clinical efficacy. Success in this area could have the added benefit of inspiring other fields in medically relevant materials research, since microbial colonization of medical implants and devices is a ubiquitous problem in the field.